Public policies for housing in colombia. aim conflicts (2008)
The purpose of this article is to illustrate how two precepts included in the article 51 of the Political Constitution of Colombia, occasionally oppose one to the other. The first precept is referred to the right of every citizen to accede to dignifying housing and to the State obligation to provide it; the second precept is referred to the endorsement for housing plans and to the adequate funding. After reviewing the main contents of norms where the precepts are developed, implicit and explicit decisions are identified; there are also reviewed the impacts that the application of norms has on the housing production –to say so, the way the decisions are being materialized–. The conflicted precepts resolution is perceived in the bad quality of constructions and in the difficulty to obtain housing against the fulfillment of constitutional rights. The article concludes supporting the argument that the configuration of management processes of public policies must be understood as wide, including and complex social process.